Brand environment design. - Van Rijn, Marike, ....-; Smith, Jim, ....- (Amsterdam : Bis, 2004)
Designers make the merits of a brand visible and tangible. Brand Environment Design designs a rendezvous with brand customers in such a way that a valuable and effective interaction takes place. Each element of the created environment has been chosen with a purpose and contributes to a total brand experience. The design builds on the strong aspects of a brand, while simultaneously arousing curiosity through the use of surprising and unexpected elements. The ultimate goal during the design process is to strike a balance between stimulating emotions and an agreeable environment where brands are shown off to their full advantage and customers find what they're looking for. This book describes QuA's passion for bringing brands to life. With a survey of eighteen years of work, it soon becomes clear that passion is a powerful agent for effectively and aesthetically translating ideas into practice. Brand Environment Design has been compiled by QuA Associates, a multidisciplinary design agency with wide experience in interior design, multimedia and graphic design
Keywords: Industrieel ontwerpen; Vormgeving